Pengaruh Motivasi Dan Lingkungan Kerja Terhadap Kinerja Pegawai Di Puskesmas Garuda Kecamatan Andir Kota Bandung - Mulyana, Hari; Suryanto, Suryanto; Hidayat, Asep Iwa (SEIKO : Journal of Management & Business, 2023)
This study aims to examine the influence of motivation and work environment on employee performance in Puskesmas Garuda, Andir District, Bandung City. The research sample consisted of 95 employees of Puskesmas Garuda selected randomly. Data were collected using questionnaires that measured the variables of work motivation, work environment, and employee performance. Path analysis was employed to analyze the relationships among these variables. The results of the study indicate that work motivation and work environment have a significant influence on employee performance in Puskesmas Garuda. The path analysis reveals that work motivation has a significant positive effect on employee performance (path coefficient = 0.55, p < 0.05), while the work environment also has a significant positive influence on employee performance (path coefficient = 0.42, p < 0.05). These findings suggest that effective management of work motivation and work environment can enhance employee performance in Puskesmas Garuda. Management needs to pay sufficient attention to employee work motivation by creating a conducive work environment and providing appropriate support. Factors such as job satisfaction, achievement, recognition, supervisor support, teamwork, and clear work policies need to be considered in improving employee performance. This study provides a better understanding of the importance of work motivation and work environment in enhancing employee performance in Puskesmas Garuda. The findings can serve as a basis for Puskesmas management to develop strategies and policies that support the improvement of work motivation and a conducive work environment, thereby enhancing employee performance and the quality of services provided in Puskesmas Garuda. Keywords: work motivation, work environment, employee performance, path analysis.